Perceraian dan Perzinahan: Suatu Pendekatan Tafsir Feminis terhadap Matius 5:27-32 - Novian Dias; H Talaway; Monike Hukubun (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2020)
Cases of divorce and adultery are found in the context of society today. The issue of divorce and adultery is also discussed in the biblical text with its context. One of them is the Gospel of Matthew, which addresses these two cases in an inseparable frame. It is interesting that divorce issues that occur are often associated with adultery committed by one partner and harming the other party. The divorce case described by Matthew is not desired by Jesus. Jesus is depicted as a character who defends women but does not rule out men. In establishing family ties, men and women are expected to have the same responsibility to maintain the sanctity of the marital relationship that has been built. This study uses library research to produce interpretations and study of the text of the Gospel of Matthew 5: 27-32 by paying attention to women's experiences using a feminist perspective.